2011
DOI: 10.3109/00498254.2011.604743
|View full text |Cite
|
Sign up to set email alerts
|

Flavin monooxygenases, FMO1 and FMO3, not cytochrome P450 isoenzymes, contribute to metabolism of anti-tumour triazoloacridinone, C-1305, in liver microsomes and HepG2 cells

Abstract: 5-Dimethylaminopropylamino-8-hydroxytriazoloacridinone, C-1305, being the close structural analogue of the clinically tested imidazoacridinone anti-tumour agent, C-1311, expressed high activity against experimental tumours and is expected to have more advantageous pharmacological properties than C-1311. The aim of this study was to elucidate the role of selected liver enzymes in the metabolism of C-1305. We demonstrated that the studied triazoloacridinone was transformed with rat and human liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…We showed that cytochrome P450 enzymes were not involved in C-1305 or C-1311 activation, but both compounds were selective irreversible inhibitors of CYP1A2 and CYP3A4 but not of CYP2 family isoforms (Fedejko-Kap et al, 2011;Potega et al, 2011). The metabolites observed with rat and human microsomes, as well as with human hepatocellular liver carcinoma cell line (HepG2) cells, were shown to be flavin monooxygenase (FMO)-mediated Nv-oxide derivatives in the aminoalkyl side chain.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…We showed that cytochrome P450 enzymes were not involved in C-1305 or C-1311 activation, but both compounds were selective irreversible inhibitors of CYP1A2 and CYP3A4 but not of CYP2 family isoforms (Fedejko-Kap et al, 2011;Potega et al, 2011). The metabolites observed with rat and human microsomes, as well as with human hepatocellular liver carcinoma cell line (HepG2) cells, were shown to be flavin monooxygenase (FMO)-mediated Nv-oxide derivatives in the aminoalkyl side chain.…”
Section: Introductionmentioning
confidence: 91%
“…The metabolites observed with rat and human microsomes, as well as with human hepatocellular liver carcinoma cell line (HepG2) cells, were shown to be flavin monooxygenase (FMO)-mediated Nv-oxide derivatives in the aminoalkyl side chain. Identical metabolites were found with the human recombinant flavin-containing monooxygenases FMO1 and FMO3 (Fedejko-Kap et al, 2011;Potega et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, both compounds were shown to inhibit the activity of human recombinant and microsomal CYP1A2 and CYP3A4 (Fedejko-Kap et al, 2011;Potega et al, 2011), which suggested the formation of some reactive intermediates, followed by covalent binding to the active center of the enzyme. Furthermore, the 8-hydroxyl group of C-1311 participated in peroxidase-mediated metabolism, which produced reactive intermediates susceptible to substitution in the presence of cellular nucleophiles (Mazerska et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown previously that although cytochrome P450s are not involved in C-1305 or C-1311 activation, both compounds are selective irreversible inhibitors of CYP1A2 and CYP3A4 but not CYP2 isoforms (Fedejko-Kap et al, 2011;Potega et al, 2011). Each compound was also found to be metabolized by rat liver microsomes (RLM) and human liver microsomes (HLM) to N -oxide derivatives in the aminoalkyl side chain.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation